The Evolutionarily Conserved Serine Residues in BRI1 LRR Motifs Are Critical for Protein Secretion - Chen, Tianshu; Wang, Bin; Wang, Fangfang; Niu, Guanting; Zhang, Shuo; Li, Jianming; Hong, Zhi (Frontiers in Plant Science, 2020)
As a well-studied leucine-rich-repeat receptor like kinases (LRR-RLKs) in Arabidopsis (Arabidopsis thaliana), BRI1 functions as a cell surface receptor for sensing the smallest ligand molecule identified thus far. A weak allele bri1-9 (S662F) harboring a mutation at the conserved serine (Ser*) residue among 25 LRRs leads to the protein retention in the ER. However, it is still less known about the importance of these residues. Through site-directed mutagenesis and phenotypic complementation test, we examined the effects of these conserved serine residues on protein secretion and functions. The results showed that the replacements of these serine residues significantly changed the sub-localization of bri1-GFPs to the ER and the rigid space constrains as well as the requirement of successive inner polar contact existed on these sites. In addition, the continuous presence of Ser* was mainly disrupted at the LRR-island domain interface and the changes of these four non-serine residues to serine greatly decreased the protein ability to complement bri1-301 compact phenotype and the BR signaling activation. From sequence alignment, the other known LRR-RLK also harbored the S*-chain and the non-Ser* residues at ligand binding region along the S*-chain as well, implying an evolutionary significance of residues at these sites in plant LRR-RLKs.